Social Bullying Among Undergraduates: The Roles of Internet Gaming Disorder, Risk-Taking Behavior, and Internet Addiction - Nwanosike, Chinonso L.; Ujoatuonu, Ikechukwu V. N.; Kanu, Gabriel C.; Ike, Obinna O.; Okeke, Tochukwu J. (Frontiers in Psychology, 2022)
An issue that affects the academic engagement, performance, health and wellbeing of university undergraduates is bullying. A substantial literature has examined the predictors of bullying perpetration, but there is little research on the contributions of internet-related factors and the propensity to take risks in bullying. We examined the roles of internet gaming disorder, risk-taking behaviour, and internet addition in social bullying. Four instruments were for data collection, namely: Young Adult Social Behavior Scale (YASB), the Internet Gaming Disorder Scale (IGDS9-SF), Domain-Specific Risk-Taking Scale, and the Internet Addiction Test Scale. Participants were Five hundred and fifty-two (552) undergraduates from the University of Nigeria, Nsukka consisting of 143 males and 409 females (age range = 17 to 32 years; M = 21.45; SD = 2.71). Results of regression analysis showed that gaming disorder and risk-taking behaviour had positive associations with social bullying. Thus, the more people grow addicted to internet gaming and take more risks, the more they are likely to become bullies. Internet addiction had no significant association with social bullying. Efforts should be made to minimize the rate of dysfunctional internet use and risk-taking behaviours of undergraduates in order to curtail bullying perpetration.